L’infrastructure verte dans l’aire urbaine de Montréal: la multifonctionnalité des espaces végétalisés en question - Xavier Cornet (Éditions en environnement VertigO, 2021)
Over the last ten years or so, there has been a growing interest among researchers in green infrastructure, which aims to improve the quality of life of inhabitants through the use of ecosystem services. More specifically, we are witnessing a networking of urban green spaces in order to increase their resilience in the face of disturbances (habitat degradation, poor management practices, insufficient genetic mixing, etc.). This multifunctionality of green spaces will be questioned in the Montreal agglomeration. The vegetal landscape will be taken into account through its ecological quality and the uses that urbanites make of it. This vegetal landscape will be mobilized through maps of plant formations identified by their dominant species, which allows for a finer approach than most research on green infrastructure using satellite images. A criterion-based evaluation will enable us to assess the ecological quality and social interest of green spaces according to their location in the urban space. In addition, Montréal has developed a planning tool that corresponds to the definitions of green infrastructure, the ecoterritories. The opportunities for the development of green infrastructure will be compared to the availability of these ecoterritories, with a stand point to evaluate their potential.